Super-hydrophobic hemp fabric and preparation method thereof

By mixing the low-surface energy substance of lotus leaves with coating agent and pore-forming agent, a composite coating agent is formed, and the coating finishing and ultrasonic washing technology is used to adhere to the surface of cannabis fabrics, the problem of poor hydrophobic performance of existing cannabis fabrics is solved, the superhydrophobicity of cannabis fabrics is achieved, and the scope of application is expanded.

CN119754044APending Publication Date: 2025-04-04WUHAN TEXTILE UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510160281.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing hemp fabric has poor hydrophobic properties, which limits its application in self-cleaning, oil-water separation and other fields.

Method used

By extracting and preparing the low-surface energy substances in lotus leaves into emulsions, mixing them with coating agent and pore-forming agent solutions, a composite coating agent is formed, and through coating finishing and ultrasonic washing technology, it adheres to the surface of the hemp fabric, enhancing its hydrophobicity.

Benefits of technology

The hydrophobicity of cannabis fabrics is significantly improved, and the apparent contact angle range of water droplets is between 152° and 156°, and after 10 washes, the hydrophobic performance has not been significantly weakened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005270835310000111
    Figure BDA0005270835310000111
Patent Text Reader

Abstract

The invention relates to a super-hydrophobic hemp fabric and a preparation method thereof. The fabric can be prepared by the following method: firstly, preparing a coating agent from acrylic acid, butyl acrylate and the like; secondly, extracting low-surface-energy substances in the lotus leaves, and preparing the low-surface-energy substances into emulsion; thirdly, mixing the coating agent, the emulsion and the pore-forming agent solution to prepare a composite coating agent; secondly, the hemp fabric is subjected to coating finishing; finally, the finished hemp fabric is subjected to ultrasonic washing and drying, and the super-hydrophobic hemp fabric is prepared. The surface of the prepared super-hydrophobic hemp fabric contains low-surface-energy substances in lotus leaves, the apparent contact angle range of water drops on the hemp fabric ranges from 152 degrees to 156 degrees, and the super-hydrophobic hemp fabric shows good super-hydrophobicity; after 10 times of water washing, the hydrophobicity of the hemp fabric is still not obviously weakened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fabric preparation, and particularly relates to a super-hydrophobic hemp fabric and a preparation method thereof. Background Art

[0002] With the continuous development of new textile materials and technologies, the types of textiles are increasing, and people's demand for functional textiles is also growing. Superhydrophobic surfaces have a wide range of applications in self-cleaning, fluid drag reduction, antibacterial materials, corrosion resistance, anti-icing and oil-water separation, because of their water contact angle (WCA) greater than 150°. In the past 20 years, due to the lotus effect of lotus leaves, people's interest in superhydrophobic surfaces has increased dramatically.

[0003] Hemp fabric is a fabric woven from hemp fiber. The polygonal middle structure of hemp fiber and the dense longitudinal cracks on the outer surface make it a "shield" against moisture. Hemp fiber not only has a high moisture absorption rate, but also has a strong moisture release function. The ventilated and non-humid environment does not provide a breeding ground for bacteria. In addition to defense, hemp fiber also has an inherent "killer weapon". Hemp fiber contains phenolic substances that can destroy the life activities of mold microorganisms, hinder the metabolism and physiological activities of mold, destroy the bacterial structure, and ultimately inhibit the growth and reproduction of microorganisms. Therefore, hemp fiber has excellent properties of anti-mildew and antibacterial, moisture absorption and breathability, sweat wicking and deodorization, and is widely used in bedding fabrics, automotive textiles, and clothing fabrics.

[0004] Literature surveys and studies have shown that there are few studies on the preparation process of super-hydrophobic hemp fabrics, while the preparation of other specific properties of hemp fibers has received widespread attention, such as: China Invention Patent Application No. 202011352770.4 discloses a method for preparing hemp health-care fibers: This application is to soften hemp fibers and produce functional effects by enzyme treatment, and has a fragrant smell, which is used to prepare functional health-care clothing; China Invention Patent Application No. 201911322833.9 discloses a hemp fiber composite insulation material and a preparation method thereof: hemp composite fibers are prepared using expanded perlite, silica sol, hexadecyltrimethylammonium bromide, deionized water, 4% alkaline water and environmentally friendly glue. The specific performance hemp fabrics prepared by the above method still have shortcomings, such as the poor hydrophobicity of the existing hemp fabrics, which has great development space in self-cleaning, oil-water separation, etc., which leads to the limitation of the application range of hemp fabrics. Therefore, improving the preparation process of the existing specific performance hemp fabrics so that they also have excellent super-hydrophobic properties has important practical significance for the wider application of hemp fabrics. Summary of the invention

[0005] In view of the above-mentioned drawbacks existing in the prior art, the object of the present invention is to provide a super hydrophobic hemp fabric and a preparation method thereof.

[0006] The purpose of the present invention is to provide a super-hydrophobic hemp fabric, which has the characteristics of being environmentally friendly and human-friendly. The fabric can be prepared by the following method: first, a coating agent is prepared by using acrylic acid, butyl acrylate and the like; second, low surface energy substances in lotus leaves are extracted and prepared into an emulsion; third, the coating agent, the emulsion and a pore-forming agent solution are mixed to prepare a composite coating agent; third, the hemp fabric is subjected to coating finishing; finally, the finished hemp fabric is subjected to ultrasonic water washing and drying to prepare the super-hydrophobic hemp fabric.

[0007] The object of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a super-hydrophobic hemp fabric comprises the following steps:

[0009] (1) Preparation of coating agent: Weigh sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10), acrylic acid, styrene, butyl acrylate and ammonium persulfate, dissolve all of the sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10) and 1 / 3 of the total amount of acrylic acid, styrene, butyl acrylate and ammonium persulfate initiator in deionized water, stir evenly, control the temperature to 75-85°C, and stir for 1-2 hours; then, dissolve the remaining 2 / 3 of acrylic acid, butyl acrylate and ammonium persulfate initiator in deionized water and add dropwise to the mixed solution just stirred, control the dropping time to 2-3 hours, and keep warm for 2-3 hours after the dropping is completed; the emulsion is left for one month, and the coating agent is obtained if no stratification or precipitation occurs.

[0010] Preferably, the dosage ratio of the sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10), acrylic acid, styrene, butyl acrylate and ammonium persulfate is: 1g: (1-2)g: (0.1-0.2)mol: (0.1-0.2)mol: (0.1-0.2)mol: (0.5-1)g.

[0011] (2) Extraction of low surface energy substances from lotus leaves: Select lotus leaves, wash them and then crush them, extract them using supercritical CO2, and use ethanol as an entrainer to obtain an extract, which is an ethanol solution containing low surface energy substances on the lotus leaf surface; distill the extract under reduced pressure to remove the solvent and obtain low surface energy substances.

[0012] Preferably, the extraction pressure is 10-20 MPa, the extraction temperature is 50-60° C., the extraction time is 1-3 h, and the CO2 flow rate is 20-30 L / h.

[0013] (3) Emulsification of lotus leaf low surface energy material: Take the low surface energy material obtained in step (2) into a round-bottom flask, add dichloromethane, and continue stirring to dissolve it; after it is dissolved, add Span 60 and stir to mix it evenly; add the above mixed solution dropwise into a saturated sodium dodecyl sulfate aqueous solution, and stir evenly with a magnetic rotor to obtain an O / W type emulsion.

[0014] Preferably, the amount ratio of the low surface energy substance obtained in step (2), Span 60 and dichloromethane is: 1g: (0.2-0.4)g: (20-40)mL; the amount ratio of the mixed solution to the saturated sodium dodecyl sulfate aqueous solution is 1mL: (3-5)mL.

[0015] (4) Preparation of pore-forming agent solution: Dissolve fatty alcohol polyoxyethylene ether (AEO-9) in tap water to prepare a pore-forming agent solution.

[0016] Preferably, the usage ratio of the fatty alcohol polyoxyethylene ether (AEO-9) to tap water is 1 g: (100-200) mL.

[0017] (5) Blending: The coating agent prepared in step (1), the O / W type emulsion prepared in step (3), and the pore-forming agent solution prepared in step (4) are uniformly mixed by a high-speed dispersing homogenizer to prepare a composite coating agent.

[0018] Preferably, the dosage ratio of the coating agent prepared in step (1), the O / W type emulsion prepared in step (3), and the pore-forming agent solution prepared in step (4) is 1 mL: (0.1-0.2) mL: (0.01-0.03) mL.

[0019] Preferably, the rotation speed of the high-speed dispersing homogenizer is 20,000 to 30,000 r / min; and the mixing time is 5 to 15 minutes.

[0020] (6) Coating finishing: The fabric is stretched tightly on a stretcher, and the composite coating agent prepared in step (5) is evenly applied on the fabric with a scraper, with a coating amount of 4 to 8 g / m2 dry weight. 2 , drying at 70-90°C for 3-5 minutes, baking at 110-120°C for 2-4 minutes, to obtain the coated hemp fabric.

[0021] Preferably, the fabric is hemp fabric.

[0022] (7) Surface treatment: Under the assistance of ultrasound, the coated hemp fabric is immersed in tap water and ultrasonically cleaned for 5 to 7 times. Finally, it is dried to obtain a super-hydrophobic hemp fabric.

[0023] Preferably, the usage ratio of the coated hemp fabric to tap water is 1 g: (100-200) mL.

[0024] The present invention has the following notable features:

[0025] (1) The low surface energy substance in lotus leaves is a good hydrophobic material, but it is difficult to apply it to the field of textile fabrics. The present invention extracts the low surface energy substance in lotus leaves and prepares it into an emulsion, then uniformly mixes the emulsion, a pore-forming agent solution and a coating agent to obtain a composite coating agent; the coating agent is attached to the surface of hemp fabric through a coating finishing technology, and the inventor of the present application unexpectedly finds that the hydrophobicity of the hemp fabric is significantly improved.

[0026] (2) In order to increase the surface roughness of hemp fabric, the inventors of the present application unexpectedly discovered that by introducing fatty alcohol polyoxyethylene ether (AEO-9) into the composite coating agent and then removing it by ultrasonic water washing, a rough micro-nano structure was formed on the surface of the hemp fabric, which significantly enhanced the hydrophobicity of the hemp fabric.

[0027] (3) The surface of the super-hydrophobic hemp fabric prepared by the present invention contains low surface energy substances in lotus leaves, and the apparent contact angle of water droplets on the hemp fabric ranges from 152° to 156°, showing good super-hydrophobicity; after 10 times of water washing, the hydrophobicity of the hemp fabric is still not significantly weakened.

[0028] (4) The super-hydrophobicity of the super-hydrophobic hemp fabric prepared by the present invention is not significantly weakened after being washed 10 times, which indicates that low surface energy substances can be firmly attached to the surface of the hemp fabric.

[0029] (5) The super-hydrophobic hemp fabric prepared by the present invention has a wide range of raw material sources, a simple preparation process, and has a good market promotion prospect. DETAILED DESCRIPTION

[0030] Source of main raw materials: Fatty alcohol polyoxyethylene ether (AEO-9) was purchased from Nanjing Wanghua Chemical Co., Ltd.

[0031] The following examples and comparative examples illustrate the present invention in detail.

[0032] Example 1

[0033] In this embodiment, a method for preparing a super-hydrophobic hemp fabric is provided, and the method comprises the following steps:

[0034] (1) Preparation of coating agent: Weigh 1 g of sodium dodecylbenzene sulfonate, 1.5 g of octylphenol polyoxyethylene ether (OP-10), 0.15 mol of acrylic acid, 0.15 mol of styrene, 0.15 mol of butyl acrylate and 0.75 g of ammonium persulfate, dissolve all of the sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10) and 1 / 3 of the total amount of acrylic acid, styrene, butyl acrylate and ammonium persulfate initiator in 300 mL of deionized water, stir evenly, control the temperature to 80° C., and stir for 1.5 h; then, dissolve the remaining 2 / 3 of acrylic acid, butyl acrylate and ammonium persulfate initiator in 300 mL of deionized water and add dropwise to the mixed solution just stirred, the dropping time is controlled to 2.5 h, and after the dropping is completed, keep the temperature for 2.5 h. The coating agent can be obtained by leaving the emulsion for one month without stratification or precipitation.

[0035] (2) Extraction of low surface energy substances from lotus leaves: Select lotus leaves, wash them and then crush them, extract them using supercritical CO2, use ethanol as an entrainer, the extraction pressure is 15 MPa, the extraction temperature is 55°C, the extraction time is 2 h, and the CO2 flow rate is 25 L / h to obtain an extract, which is an ethanol solution containing low surface energy substances on the lotus leaf surface; the extract is subjected to reduced pressure distillation to remove the solvent to obtain low surface energy substances.

[0036] (3) Emulsification of lotus leaf low surface energy material: Take 1 g of the low surface energy material obtained in step (2) into a round-bottom flask, add 30 mL of dichloromethane, and continue stirring to dissolve it; after it is dissolved, add 0.3 g of Span 60 and stir to mix it evenly; add the above mixed solution dropwise into 120 mL of saturated sodium dodecyl sulfate aqueous solution, and stir evenly with a magnetic rotor to obtain an O / W type emulsion.

[0037] (4) Preparation of pore-forming agent solution: Dissolve 1 g of fatty alcohol polyoxyethylene ether (AEO-9) in 150 mL of tap water to prepare a pore-forming agent solution.

[0038] (5) Blending: 1000 mL of the coating agent prepared in step (1), 150 mL of the O / W type emulsion prepared in step (3), and 20 mL of the pore-forming agent solution prepared in step (4) were uniformly mixed by a high-speed disperser homogenizer at a speed of 25000 r / min; the mixing time was 10 minutes to obtain a composite coating agent.

[0039] (6) Coating finishing: The hemp fabric is stretched tightly on a stretcher, and the composite coating agent prepared in step (5) is evenly applied on the fabric with a scraper, with a coating amount of 6 g / m2 by dry weight. 2 , dried at 80°C for 4 minutes and baked at 115°C for 3 minutes to obtain the coated hemp fabric.

[0040] (7) Surface treatment: Under the assistance of ultrasound, the coated hemp fabric was immersed in tap water, the dosage ratio of the coated hemp fabric to tap water was 1 g: 150 mL, and ultrasonic cleaning was performed 6 times. Finally, the hemp fabric was dried to obtain a superhydrophobic hemp fabric.

[0041] Example 2

[0042] In this embodiment, a method for preparing a super-hydrophobic hemp fabric is provided, and the preparation method comprises the following steps:

[0043] (1) Preparation of coating agent: Weigh 1 g of sodium dodecylbenzene sulfonate, 1.0 g of octylphenol polyoxyethylene ether (OP-10), 0.1 mol of acrylic acid, 0.1 mol of styrene, 0.1 mol of butyl acrylate and 0.5 g of ammonium persulfate, dissolve all of the sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10) and 1 / 3 of the total amount of acrylic acid, styrene, butyl acrylate and ammonium persulfate initiator in 300 mL of deionized water, stir evenly, control the temperature to 75° C., and stir for 1.0 h; then, dissolve the remaining 2 / 3 of acrylic acid, butyl acrylate and ammonium persulfate initiator in 300 mL of deionized water and add dropwise to the mixed solution just stirred, the dropping time is controlled to 2.0 h, and after the dropping is completed, keep warm for 2.0 h. The emulsion is left for one month, and the coating agent is obtained if no stratification or precipitation occurs.

[0044] (2) Extraction of low surface energy substances from lotus leaves: Select lotus leaves, wash them and then crush them, extract them using supercritical CO2, use ethanol as an entrainer, the extraction pressure is 10 MPa, the extraction temperature is 50°C, the extraction time is 1 h, and the CO2 flow rate is 20 L / h to obtain an extract, which is an ethanol solution containing low surface energy substances on the lotus leaf surface; the extract is subjected to reduced pressure distillation to remove the solvent to obtain low surface energy substances.

[0045] (3) Emulsification of lotus leaf low surface energy material: Take 1 g of the low surface energy material obtained in step (2) into a round-bottom flask, add 20 mL of dichloromethane, and continue stirring to dissolve it; after it is dissolved, add 0.2 g of Span 60 and stir to mix it evenly; add the above mixed solution dropwise into 60 mL of saturated sodium dodecyl sulfate aqueous solution, and stir evenly with a magnetic rotor to obtain an O / W type emulsion.

[0046] (4) Preparation of pore-forming agent solution: Dissolve 1 g of fatty alcohol polyoxyethylene ether (AEO-9) in 100 mL of tap water to prepare a pore-forming agent solution.

[0047] (5) Blending: 1000 mL of the coating agent prepared in step (1), 100 mL of the O / W type emulsion prepared in step (3), and 10 mL of the pore-forming agent solution prepared in step (4) are uniformly mixed by a high-speed disperser homogenizer at a speed of 20,000 r / min; the mixing time is 5 minutes, and a composite coating agent is obtained.

[0048] (6) Coating finishing: The hemp fabric is stretched tightly on a stretcher, and the composite coating agent prepared in step (5) is evenly applied on the fabric with a scraper, with a coating amount of 4 g / m2 dry weight. 2 , dried at 70°C for 3 minutes, and baked at 110°C for 2 minutes to obtain the coated hemp fabric.

[0049] (7) Surface treatment: Under the assistance of ultrasound, the coated hemp fabric was immersed in tap water, the dosage ratio of the coated hemp fabric to tap water was 1 g: 100 mL, and ultrasonic cleaning was performed 5 times. Finally, it was dried to obtain a superhydrophobic hemp fabric.

[0050] Example 3

[0051] In this embodiment, a method for preparing a super-hydrophobic hemp fabric is provided, and the method comprises the following steps:

[0052] (1) Preparation of coating agent: Weigh 1 g of sodium dodecylbenzene sulfonate, 2 g of octylphenol polyoxyethylene ether (OP-10), 0.2 mol of acrylic acid, 0.2 mol of styrene, 0.2 mol of butyl acrylate and 1 g of ammonium persulfate, dissolve all of the sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10) and 1 / 3 of the total amount of acrylic acid, styrene, butyl acrylate and ammonium persulfate initiator in 300 mL of deionized water, stir evenly, control the temperature to 85° C., and stir for 2 h; then, dissolve the remaining 2 / 3 of acrylic acid, butyl acrylate and ammonium persulfate initiator in 300 mL of deionized water and add dropwise to the mixed solution just stirred, the dropping time is controlled to 3 h, and after the dropping is completed, keep warm for 3 h; the emulsion is left for one month, and the coating agent is obtained if no stratification or precipitation occurs.

[0053] (2) Extraction of low surface energy substances from lotus leaves: Select lotus leaves, wash them and then crush them, extract them using supercritical CO2, use ethanol as an entrainer, the extraction pressure is 20 MPa, the extraction temperature is 60°C, the extraction time is 3 h, and the CO2 flow rate is 30 L / h to obtain an extract, which is an ethanol solution containing low surface energy substances on the lotus leaf surface; the extract is subjected to reduced pressure distillation to remove the solvent to obtain low surface energy substances.

[0054] (3) Emulsification of lotus leaf low surface energy material: Take 1 g of the low surface energy material obtained in step (2) into a round-bottom flask, add 40 mL of dichloromethane, and continue stirring to dissolve it; after it is dissolved, add 0.4 g of Span 60 and stir to mix it evenly; add the above mixed solution dropwise into 200 mL of saturated sodium dodecyl sulfate aqueous solution, and stir evenly with a magnetic rotor to obtain an O / W type emulsion.

[0055] (4) Preparation of pore-forming agent solution: Dissolve 1 g of fatty alcohol polyoxyethylene ether (AEO-9) in 200 mL of tap water to prepare a pore-forming agent solution.

[0056] (5) Blending: 1000 mL of the coating agent prepared in step (1), 200 mL of the O / W type emulsion prepared in step (3), and 30 mL of the pore-forming agent solution prepared in step (4) are uniformly mixed by a high-speed disperser homogenizer at a speed of 30,000 r / min; the mixing time is 15 minutes to obtain a composite coating agent.

[0057] (6) Coating finishing: The hemp fabric is stretched tightly on a stretcher, and the composite coating agent prepared in step (5) is evenly applied on the fabric with a scraper, with a coating amount of 8 g / m2 dry weight. 2 , dried at 90°C for 5 minutes and baked at 120°C for 4 minutes to obtain the coated hemp fabric.

[0058] (7) Surface treatment: Under the assistance of ultrasound, the coated hemp fabric was immersed in tap water, the dosage ratio of the coated hemp fabric to tap water was 1 g: 200 mL, and ultrasonic cleaning was performed 7 times. Finally, it was dried to obtain a superhydrophobic hemp fabric.

[0059] Comparative Example A

[0060] Taking Example 1 as a comparison, in this comparative example, the raw material composition of the coating agent is changed, that is, "acrylic acid" in step (1) is replaced by "methyl acrylate", and the other preparation methods are implemented according to the preparation method of Example 1.

[0061] Comparative Example B

[0062] Taking Example 1 as a comparison, in this comparative example, the low surface energy material in the lotus leaf is not selected, that is, step (2) and step (3) are not implemented, and the other preparation methods are implemented according to the preparation method of Example 1.

[0063] Comparative Example C

[0064] Taking Example 1 as a comparison, in this comparative example, the pore-forming agent is changed, that is, the "fatty alcohol polyoxyethylene ether (AEO-9)" in step (4) is replaced by "sodium dodecyl sulfate", and the other preparation methods are implemented according to the preparation method of Example 1.

[0065] Comparative Example D

[0066] Taking Example 1 as a comparison, in this comparative example, ultrasonic assistance is not used, that is, step (7) "under ultrasonic assistance" is deleted, and other preparation methods are implemented according to the preparation method of Example 1.

[0067] Super hydrophobic performance test:

[0068] In order to better detect the super-hydrophobicity of the super-hydrophobic hemp fabric prepared in the present invention, the super-hydrophobic hemp fabrics a, b, c, d, e, f, g, and h prepared in the above-mentioned specific embodiments 1 to 3 and comparative examples A to D of the present invention are selected. The apparent contact angle of water droplets on the surface of the super-hydrophobic hemp fabric is measured by using the XG-CAMA1 basic contact angle tester, and no less than 30 test samples are tested, and the test average value is taken. The fabric to be tested is washed in a standard manner according to the washing method of the washing color fastness tester of GB / T 20944.1-2007, and the super-hydrophobic properties of the initial sample and the sample after washing 10 times are tested. The test results are shown in Table 1.

[0069] Table 1 Apparent contact angles of water droplets on superhydrophobic hemp fabrics a, b, c, d, e, f, g

[0070]

[0071] As can be seen from Table 1, when not washed, the apparent contact angle of water droplets on super-hydrophobic hemp fabrics a, b, and c ranges from 152° to 156° respectively; after 10 washes, the hydrophobic properties of fabrics a, b, and c are still not significantly weakened; it can be considered that the super-hydrophobic hemp fabric prepared by the present invention has super-hydrophobicity. The super-hydrophobicity of super-hydrophobic hemp fabrics d, e, f, g, and h prepared in Comparative Examples AE is significantly poor, which shows that the raw material composition of the coating agent, the selection of the pore-forming agent, the selection of the low surface energy material in the lotus leaf, and the ultrasonic assistance all have an important influence on the super-hydrophobicity of the hemp fabric.

Claims

1. A method for preparing super hydrophobic hemp fabric, characterized in that: The preparation method comprises the following steps: (1) Preparation of coating agent: Weigh sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10), acrylic acid, styrene, butyl acrylate and ammonium persulfate, dissolve all of sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10) and 1 / 3 of the total amount of acrylic acid, styrene, butyl acrylate and ammonium persulfate initiator in deionized water, stir evenly, control the temperature to 75-85° C., and stir for 1-2 hours; then, dissolve the remaining 2 / 3 of acrylic acid, butyl acrylate and ammonium persulfate initiator in deionized water and add dropwise to the mixed solution just stirred, control the dropwise addition time to 2-3 hours, and keep warm for 2-3 hours after the dropwise addition is completed; the emulsion is left for one month, and the coating agent is obtained if no stratification or precipitation occurs; (2) Extraction of low surface energy substances from lotus leaves: Select lotus leaves, wash them and then crush them, extract them using supercritical CO2, use ethanol as an entrainer, and prepare an extract, which is an ethanol solution containing low surface energy substances on the surface of the lotus leaves; perform reduced pressure distillation on the extract to remove the solvent and prepare low surface energy substances; (3) Emulsification of lotus leaf low surface energy material: Take the low surface energy material obtained in step (2) into a round-bottom flask, add dichloromethane, and continue stirring to dissolve it; after it is dissolved, add Span 60 and stir to mix it evenly; add the above mixed solution dropwise into a saturated sodium dodecyl sulfate aqueous solution, and stir evenly with a magnetic rotor to obtain an O / W type emulsion; (4) Preparation of pore-forming agent solution: dissolving fatty alcohol polyoxyethylene ether (AEO-9) in tap water to prepare a pore-forming agent solution; (5) Blending: uniformly mixing the coating agent prepared in step (1), the O / W type emulsion prepared in step (3), and the pore-forming agent solution prepared in step (4) by a high-speed dispersing homogenizer to prepare a composite coating agent; (6) Coating finishing: The fabric is stretched tightly on a stretcher, and the composite coating agent prepared in step (5) is evenly applied on the fabric with a scraper, with a coating amount of 4 to 8 g / m2 dry weight. 2 , drying at 70-90°C for 3-5 minutes, and baking at 110-120°C for 2-4 minutes to obtain the coated hemp fabric; (7) Surface treatment: Under the assistance of ultrasound, the coated hemp fabric is immersed in tap water and ultrasonically cleaned for 5 to 7 times. Finally, it is dried to obtain a super-hydrophobic hemp fabric.

2. The method for preparing a super-hydrophobic hemp fabric according to claim 1, characterized in that: The dosage ratio of sodium dodecylbenzene sulfonate, octylphenol polyoxyethylene ether (OP-10), acrylic acid, styrene, butyl acrylate and ammonium persulfate in step (1) is: 1g: (1-2)g: (0.1-0.2)mol: (0.1-0.2)mol: (0.1-0.2)mol: (0.5-1)g.

3. The method for preparing a super hydrophobic hemp fabric according to claim 1, characterized in that: The extraction pressure in step (2) is 10-20 MPa, the extraction temperature is 50-60° C., the extraction time is 1-3 h, and the CO2 flow rate is 20-30 L / h.

4. The method for preparing a super hydrophobic hemp fabric according to claim 1, characterized in that: In step (3), the low surface energy material obtained in step (2), Span 60 and dichloromethane are used in a ratio of 1 g: (0.2-0.4) g: (20-40) mL; and the mixed solution and saturated sodium dodecyl sulfate aqueous solution are used in a ratio of 1 mL: (3-5) mL.

5. The method for preparing a super hydrophobic hemp fabric according to claim 1, characterized in that: The usage ratio of the fatty alcohol polyoxyethylene ether (AEO-9) to tap water in step (4) is 1 g: (100-200) mL.

6. The method for preparing a super hydrophobic hemp fabric according to claim 1, characterized in that: In step (5), the amount ratio of the coating agent prepared in step (1), the O / W type emulsion prepared in step (3), and the pore-forming agent solution prepared in step (4) is 1 mL: (0.1-0.2) mL: (0.01-0.03) mL; the rotation speed of the high-speed dispersing homogenizer is 20000-30000 r / min; and the mixing time is 5-15 minutes.

7. The method for preparing a super hydrophobic hemp fabric according to claim 1, characterized in that: The fabric described in step (6) is suitable for hemp fabric.

8. The method for preparing a super hydrophobic hemp fabric according to claim 1, characterized in that: The ratio of the coated hemp fabric to tap water in step (7) is 1 g: (100-200) mL.

9. A super hydrophobic hemp fabric, characterized in that: The invention is prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hemp fiber composite thermal insulation material and preparation method thereof

    CN110885206A

  • Preparation method of health-caring hemp fiber

    CN112501697A

  • Super-hydrophobic cotton fabric and preparation method thereof

    CN118895612A

  • Super-hydrophobic and antibacterial polyester fabric and preparation method thereof

    CN119083191A

  • Super-hydrophobic modal fabric and preparation method thereof

    CN119221292A